Cuff-less continuous blood pressure monitoring system using pulse transit time techniques - Wan Zaki, Wan Suhaimizan; Correia, Ricardo; Korposh, Serhiy; Hayes-Gill, Barrie R.; P. Morgan, Stephen (Penerbit UTHM, 2016)
This paper describes the development of a continuous cuff-less blood pressure system based on the pulse transit time (PTT) technique. In this study, PTT is defined by two different approaches denoted as PTT1 and PTT2. PTT1 is the time difference between the R-wave peak of the Electrocardiogram (ECG) and the peak of the Photoplethysmogram (PPG). PTT2 is the time difference between two peak PPG signals on same cardiac cycle at different positions on the body. The ECG is acquired on the chest using 3 lead electrodes and a reflection mode optical sensor is deployed on brachial artery and fingertip to monitor the PPGs. These data were synchronized using a National Instruments data acquisition card along with Matlab software for subsequent analysis. A wrist-type cuff-based blood pressure device was used to measure blood pressure on the right hand. Brachial blood pressure was measured on the upper left arm using oscillometric blood pressure monitor. Experiments were conducted by elevating the right hand at different position to investigate variability of PTT under the effects of hydrostatic pressure. Next the variability of PTT due to blood pressure changes during a Valsalva maneuver was investigated. The result shows that the PTT1 is inversely proportional to blood pressure in both experiments. Meanwhile, there is weak correlation between PTT2 and blood pressure measurement which suggests that by excluding the pre-ejection period (PEP) time in PTT calculation may reduce the accuracy of PTT for blood pressure measurement. In conclusion, PTT measurement between ECG and PPG signals has potential to be a reliable technique for cuff-less blood pressure measurement.